2013
DOI: 10.1002/glia.22501
|View full text |Cite
|
Sign up to set email alerts
|

Siglec‐h on activated microglia for recognition and engulfment of glioma cells

Abstract: Sialic-acid-binding immunoglobulin-like lectin-h (Siglec-h) is a recently identified mouse-specific CD33-related Siglec that signals via DAP12/TYROBP. Expression of Siglec-h has been observed on plasmacytoid dendritic cells and microglia, but the ligand and the function of Siglec-h remained elusive. Here, we demonstrate gene transcription and protein expression of Siglec-h by mouse microglia after interferon-γ treatment or polarization into a M1-subtype. Microglial Siglec-h acted as phagocytosis receptor since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…Corroborating this, we found that MZM in spleen (Figure 4A) and medullary macrophages in LN (data not shown) were SiglecH + by immunohistochemistry. In addition, we observed that SiglecH was expressed by CD45 int CD11b + microglia in brain (Figure 4B), in agreement with a recent study (24). …”
Section: Resultssupporting
confidence: 93%
“…Corroborating this, we found that MZM in spleen (Figure 4A) and medullary macrophages in LN (data not shown) were SiglecH + by immunohistochemistry. In addition, we observed that SiglecH was expressed by CD45 int CD11b + microglia in brain (Figure 4B), in agreement with a recent study (24). …”
Section: Resultssupporting
confidence: 93%
“…Central to MGM3 lies sialic acid binding Ig-like lectin H ( Siglech). Siglech is a putative marker of isolated microglia (Chiu et al, 2013); which modulates type I Interferon secretion associated with microglial activation and phagocytosis of glioma cells (Blasius et al, 2006; Kopatz et al, 2013). Brain specific expression and function of Siglech has yet to be completely ascertained, however, because MGM3 shows ontologies related to TLR signaling, particularly endosomal TLRs which promote interferon secretion, it is possible that Siglech is regulating this response in brain.…”
Section: Resultsmentioning
confidence: 99%
“…The research here suggests the possibility that activated microglia protect against tumours by 'stressing' the cancer cells and then phagocytosing these cells. And this is supported by evidence that microglia can phagocytose live glioma cells (Kopatz et al, 2013). However, it would be important to determine whether phagocytosis can protect against brain tumours in vivo.…”
Section: Discussionmentioning
confidence: 96%